Micro fatigue testing machine - Haftirman, Dr.; Ahmad Syayuthi, Abdul Rahman (Malaysian Invention and Design Society (MINDS), 2012)
Dr. Haftirman and his team from School of Mechatronic Engineering won gold for Micro fatigue testing machine. 23rd International Invention, Innovation and Technology Exhibition 2012 (ITEX 2012) organized by Malaysian Invention and Design Society (MINDS), 17th - 19th May 2012 at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur, Malaysia.